2014
DOI: 10.1097/jom.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

Heat Strain and Hydration Status of Surface Mine Blast Crew Workers

Abstract: Core body temperature remained within the recommended limits; however, more than 80% of workers were dehydrated before commencing the shift, and tended to remain so for the duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…A similar result was observed in Australian blast crew personal in surface mining, where 80% had a USG ≥1.020 upon commencing their shift and remained hypohydrated during and after work [27]. However, reference values for euhydration/hypohydration diagnosis are based on studies in athletes and military subjects to determine the effect of heat stress and its influence on performance [21].…”
Section: Discussionmentioning
confidence: 79%
“…A similar result was observed in Australian blast crew personal in surface mining, where 80% had a USG ≥1.020 upon commencing their shift and remained hypohydrated during and after work [27]. However, reference values for euhydration/hypohydration diagnosis are based on studies in athletes and military subjects to determine the effect of heat stress and its influence on performance [21].…”
Section: Discussionmentioning
confidence: 79%
“…For meta-analyses five and six, GRADE analysis revealed that the true effect is likely to be substantially different from the estimate of effect (very low confidence). Most (68%) 4,6,26,[33][34][35][39][40][41][42][43]45,46,[50][51][52][53][54][55]56,57, of the included studies incorporated low risk for selection bias, with the remaining studies presenting selection bias that was non-applicable (10%), 36, unclear (16%), 37,[47][48][49]118,[127][128][129][130][131][132] or, in some cases, high risk (6%) 5,38,44,133 due to acrossgroup variation in inclusion or exclusion criteria, and across-group differences in participant recruitment or selection. Most (61%) of the included studies incorporated low risk for confounding factors bias, with the remaining studies presenting confounding factor bias that was unclear (16%) 6 ,26,36,38,60,62,63,67,80,84,85,92,98-100,102,105,107-111,113,114,134-136 or high risk (23%) 33 ,35,37,44,45,47,49,59,66,74,83,86,89,91,94,96,118,127,128,132…”
Section: Resultsmentioning
confidence: 99%
“…25 In another study, which examines the state of dehydration and heat strain in fire workers in an open-pit mine, the mean radiant temperature measured 37.5°C and the average volume of urine obtained 1.024 according to the results, 73% of workers have been at least one of the symptoms of heatrelated illnesses in shift works. 26…”
Section: Introductionmentioning
confidence: 99%